Peningkatan Literasi Hijau Menuju Desa Wisata Muara Tiga Kecamatan Mulak Ulu - Sulastri, Sulastri; Adam, Mohamad; Saftiana, Yulia (Penerbit Goodwood, 2024)
Purpose: Community services aim to enhance literacy in green tourist villages in Muara Tiga Village, Mulak Ulu Subdistrict, and Lahat Regency with a focus on rural economic development. Method: Community service activities were conducted in Muara Tiga Village, Mulak Ulu Subdistrict, Lahat Regency, involving the following steps: (1) identification of village issues and potential; (2) consultation with the subdistrict and village authorities regarding the community service plan; (3) socialization of community service activities in Muara Tiga Village, Mulak Ulu Subdistrict, and Lahat Regency; (4) Green Tourist Village Literacy Training; and (5) Empowering the community to develop the tourist village. Results/Findings: The community service activities, particularly the training on